Smart, Sustainable, Resilient, and Inclusive Cities: Integrating Performance Assessment Indicators into an Ontology-Oriented Scheme in Support of the Urban Planning Practice - Maria Panagiotopoulou; Anastasia Stratigea; Margarita Kokla (Urban Science)
The unprecedented pace of urbanization has been exerting significant strain on cities, raising critical concerns across environmental, economic, social, and technological aspects. In response, the ‘Smart City’ concept has emerged as a novel urban development paradigm, aiming at addressing contemporary urban issues, enhancing cities’ competitiveness and prosperity, and fostering active participation through the strategic utilization of state-of-the-art technologies. However, the smart city term suffers from considerable conceptual ambiguity, thereby provoking intense confusion and misunderstanding among interested parties and leading to the implementation of ineffective initiatives. Moreover, the priorities of sustainability, resilience, and inclusiveness have gained prominence in the urban planning discourse, necessitating a more integrated view that aligns urban targets with performance assessment across various domains. In light of these issues, this study endeavors to clarify the above-mentioned conceptual vagueness by developing a holistic, indicator-oriented smart city ontology. The proposed knowledge representation scheme is intended to serve as a Decision Support Tool that will facilitate policymakers to tackle urban challenges and formulate sound policies. Additionally, it is expected to contribute to the fields of spatial and developmental planning by establishing a standardized framework for assessing and monitoring cities’ performance, while elucidating the complex interrelationships and trade-offs among diverse urban dimensions.